PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DANA ALOKASI KHUSUS, DANA BAGI HASIL, DERAJAT DESENTRALISASI, DAN DERAJAT KONTRIBUSI BUMD TERHADAP ALOKASI BELANJA MODAL (Pada Provinsi Kepulauan Riau) - Oviliza Haryuli; Rasuli '; Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aimed to determine the effect of fund local own revenue (PAD), general allocation fund (DAU), specific allocation fund (DAK), sharing-revenue fund (DBH), degree of decentralization, and degree of BUMD contribution againts capital expenditure. The samples which are use in this research are regency/municipality of Riau Island Province that report routine the realization report of the estimate income of regional expense (APBD) on year 2007 until 2012 from Dirjen Perimbangan Keuangan Pemerintah Daerah (www.djpkpd.go.id). The sampling method used in this study is the sample selection aims (purposive sampling method). The statistical method used to test the research hypothesis is multiple regression using SPSS 18 software. The results of this research show that fund local own revenue (PAD) has influence toward the capital expenditure, general allocation fund (DAU) has no influence toward the capital expenditure, specific allocation fund (DAK) has influence toward the capital expenditure, sharing-revenue fund (DBH) has influence toward the capital expenditure, degree of decentralization has no influence toward the capital expenditure, and the degree of BUMD contribution has influence toward the capital expenditure. Keywords: capital expenditure, fund local own revenue (PAD), general allocation fund (DAU), specific allocation fund (DAK), sharing-revenue fund (DBH), degree of decentralization, degree of BUMD contribution